Punk Culture in Contemporary China - Xiao, Jian (Springer Singapore, 2018)
This book explores for the first time the punk phenomenon in contemporary China. As China has urbanised within the context of explosive economic growth and a closed political system, urban subcultures and phenomena of alienation and anomie have emerged, and yet, the political and economic differences between China and western societies has ensured that these subcultures operate and are motivated by profoundly different structures. This book will be of interest to cultural historians, media studies and urban studies researchers, and (ex-) punk rockers. Jian Xiao, with a PhD from Loughborough University, works at Sun Yat-sen University in Guangzhou. Her research interest is focused on media and cultural studies. .